An evidenced-based, farmer-focused revival of traditional cereals - DeFries, Ruth; King, E. D. I. Oliver; Monga, Mansi; Nagendra, Harini; Neelakantan, Amrita (Frontiers in Sustainable Food Systems, 2025)
Revival of agrobiodiversity is a lynchpin for climate resilience, improved human nutrition, local economies, and cultural diversity. Following decades of decline in traditional cereals, the highest policy levels in India are promoting their revival. The revival is potentially as transformative for agriculture and diets as the Green Revolution that promoted high-yielding rice and wheat in the early 1960s and serves as a model for other places where traditional cereals are in decline. While the Green Revolution successfully increased cereal production and self-sufficiency, in hindsight critics have identified several environmental, social, and nutritional shortcomings. Efforts to revive millets can learn from these shortcomings with ground-level, systematic data collection using an adaptive management approach. Based on our observations from over 2,000 households surveys in the central Indian Highlands, we propose three principles to guide the collection of evidence for an ecologically-, nutritionally-, and socially-secure revival: (1) maintain diversity of millet species and varieties to preserve genetic resources in a rapidly changing climate; (2) ensure equitable access to technology, inputs, information and markets for all farmers; and (3) enable farmers to balance the trade-off between income from selling and nutritional benefits from consuming millets. The case study, which indicates the need for technologies to reduce drudgery from processing and attention to the income-nutrition trade-off for the poorest segments of the population, illustrates that ground-level data is needed to link high-level policy goals with field realities.